A Comprehensive Review on Microalgae‐Based Biorefinery as Two‐Way Source of Wastewater Treatment and Bioresource Recovery. Issue 3 (6th September 2022) - Malik, Sumira; Kishore, Shristi; Bora, Jutishna; Chaudhary, Vishal; Kumari, Anjali; Kumari, Preeti; Kumar, Lamha; Bhardwaj, Abhaya
Abstract: In the past few years, microalgae have gained huge recognition from the scientific community due to their potential applications in the production of a broad array of bio‐based products varying from biofuels to nanoparticles. Due to their elevated growth rate, high tolerance to various types of abiotic stresses, and complex metabolic capacity, microalgae can be used as promising tools for the attainment of a circular bioeconomy. Moreover, they can simply utilize nutrients from wastewater for biorefinery purposes, resulting in resource recovery coupled with wastewater treatment. However, due to their sub‐optimal yields and high production costs, microalgae‐based bio‐products have not yet been commercialized. This review provides insights into the employment of microalgae as an efficient bioresource for the treatment of wastewater with simultaneous enactment as a biorefinery to produce biofuels, biochar, bioplastic, fertilizers, and other high‐value bioproducts. Furthermore, the application of microalgal nanoparticles in wastewater treatment and prospects for genetic modification of microalgae for enhanced biorefinery capabilities have also been briefly highlighted. Abstract : Cultivation of microalgae on wastewater with the utilization of flue gas as a carbon source renders them potentially efficient bioresources for the treatment of wastewater with simultaneous enactment as biorefinery to produce high‐value bioproducts, including biodiesel, bioethanol, biomethane, and animal feed. This review provides insights into the employment of microalgae as an efficient bioresource for the treatment of wastewater.